Performance and Egg Weight of Laying Hens Fed on the Diets with Various By-Product Oils from the Oilseed Extraction Refinery - Senkoylu, Nizamettin; Akyurek, Hasan; Samli, H. Ersin; Yurdakurban, Nuri (Pakistan Journal of Nutrition, 2003)
To test the changes in laying performance and egg weight, four diets were added with 30 g/kg of soya oil (control), sunflower acid oil, stearin and Bergafat (acid oil). Totally hundred and ninety two brown layer hens at the age of 31 weeks were randomly allocated to 48 cage replicates. Egg production, egg weight, feed intake and feed conversion ratio of the hens receiving the diets of acid oil, stearin and Bergafat was not significantly (P>0.05) different from that of the hens receiving the diet of soya oil. The diet with Bergafat insignificantly (P>0.05) leads to reduced egg weight being 59.3 g compared to the other diets with 61.2, 61.2 and 61.9 g values, respectively. The reduced egg weight with Bergafat might be associated with the low level of unsaturated fatty acid which resulted in less lipid deposition in the egg yolk. The linoleic acid contents of studied oils ranged from 23.9, 23.0, 21.4 and 11.6 g/kg for soya oil, sunflower acid oil, stearin and Bergafat, respectively. The results indicated that the diet linoleic acid content over 12 g/kg is not critical for egg weight.